2011
DOI: 10.1017/s0962492911000079
|View full text |Cite
|
Sign up to set email alerts
|

Variationally consistent discretization schemes and numerical algorithms for contact problems

Abstract: We consider variationally consistent discretization schemes for mechanical contact problems. Most of the results can also be applied to other variational inequalities, such as those for phase transition problems in porous media, for plasticity or for option pricing applications from finance. The starting point is to weakly incorporate the constraint into the setting and to reformulate the inequality in the displacement in terms of a saddle-point problem. Here, the Lagrange multiplier represents the surface for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
194
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(196 citation statements)
references
References 320 publications
(301 reference statements)
2
194
0
Order By: Relevance
“…Since NURBS are naturally associated with higher order approximations, the extension of the dual mortar method to second order Lagrange finite elements in [26,27] including optimal a priori error estimates is also worth mentioning. A comprehensive review on dual mortar methods for contact mechanics can be found in [28,29]. In the context of domain decomposition in IGA, optimality and stability of standard mortar methods have only very recently been investigated in [30][31][32][33], where also the construction of dual B-spline basis functions has been outlined theoretically [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since NURBS are naturally associated with higher order approximations, the extension of the dual mortar method to second order Lagrange finite elements in [26,27] including optimal a priori error estimates is also worth mentioning. A comprehensive review on dual mortar methods for contact mechanics can be found in [28,29]. In the context of domain decomposition in IGA, optimality and stability of standard mortar methods have only very recently been investigated in [30][31][32][33], where also the construction of dual B-spline basis functions has been outlined theoretically [33].…”
Section: Introductionmentioning
confidence: 99%
“…The Karush-Kuhn-Tucker conditions are comprised of the impenetrability condition (34), the condition which only allows compressive tractions (35) and the complementarity condition (36). The Karush-Kuhn-Tucker conditions are shown in Figure 5 for both the penalty method and Lagrange multipliers.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In particular the inequalities given in (34)- (36) are implemented using the max-operator (see [20] for more informations) as follows Therein λ N and Φ N denote the Lagrange multiplier and corresponding constraint, respectively. Note λ N := t N denotes the exact contact traction and Φ N := g N the gap function.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective necessary and sufficient optimality conditions lead to a system of equations in R n involving Lipschitz continuous terms. Such problems are frequently solved by semi-smooth Newton methods, see [6,17,27,29] for a general theory and [7,8,19,21,28,30,36] for applications in plasticity. In this paper two methods are proposed.…”
Section: Introductionmentioning
confidence: 99%